Endosome positioning during cytokinesis. (21st May 2008) - Montagnac, Guillaume; Chavrier, Philippe
Abstract : In mammalian cells, completion of cytokinesis relies on targeted delivery of recycling membranes to the midbody. At this step of mitosis, recycling endosomes are organized as clusters located at the mitotic spindle poles as well as at both sides of the midbody. However, the mechanism that controls endosome positioning during cytokinesis is not known. Here, we discuss the possible mechanisms that drive the formation of endosomal clusters and the importance of this process for the targeted delivery of recycling membranes to the midbody.